How short or long should be a questionnaire for any research? Researchers dilemma in deciding the appropriate questionnaire length - Hunny Sharma (Saudi Journal of Anaesthesia, 2022)
A questionnaire plays a pivotal role in various surveys. Within the realm of biomedical research, questionnaires serve a role in epidemiological surveys and mental health surveys and to obtain information about knowledge, attitude, and practice (KAP) on various topics of interest. Questionnaire in border perspective can be of different types like self-administered or professionally administered and according to the mode of delivery paper-based or electronic media–based. Various studies have been conducted to assess the appropriateness of a questionnaire in a particular field and methods to translate and validate them. But very little is known regarding the appropriate length and number of questions in a questionnaire and what role it has in data quality, reliability, and response rates. Hence, this narrative review is to explore the critical issue of appropriate length and number of questions in a questionnaire while questionnaire designing.